The cell wall polysaccharides of a photosynthetic relative of apicomplexans, Chromera velia - Tortorelli, Giada; Pettolino, Filomena; Lai, De-Hua; Tomčala, Aleš; Bacic, Antony; Oborník, Miroslav; Lukeš, Julius; McFadden, Geoffrey I (Journal of phycology, 2021)
Chromerids are a group of alveolates, found in corals, that show peculiar morphological and genomic features. These organisms are evolutionary placed in-between symbiotic dinoflagellates and parasitic apicomplexans. There are two known species of chromerids: Chromera velia and Vitrella brassicaformis. Here, the biochemical composition of the C. velia cell wall was analyzed. Several polysaccharides adorn this structure, with glucose being the most abundant monosaccharide (approx. 80%) and predominantly 4-linked (approx. 60%), suggesting that the chromerids cell wall is mostly cellulosic. The presence of cellulose was cytochemically confirmed with calcofluor white staining of the algal cell. The remaining wall polysaccharides, assuming structures are similar to those of higher plants, are indicative of a mixture of galactans, xyloglucans, heteroxylans, and heteromannans. The present work provides, for the first time, insights into the outermost layers of the photosynthetic alveolate C. velia.
Keywords: Photosynthesis; monosaccharide linkage analysis; buněčná stěna; chromerids; cellulose; cell wall; Polysaccharides; polysacharidy; fotosyntéza; Phylogeny; Chromera velia; fylogeneze; Cell Wall; Alveolata; calcofluor white